Reconstructing the Muslim American Identity Through Religious Rituals and Traditions in: Khaled Hosseini’s The Kite Runner and Mohja Kahf’s The Girl in The Tangerine Scarf - Mrs .Moufida Boumous (biblio centrale, université laghouat, 2015)
The present research delves into the process of identity formation at its core the paradigm of religion. Recent research has highlighted the crucial role of religion in Muslim Americans identification and the making of identity especially in the aftermath of 9/11 events and the U.S war on terror which have distorted the image of Islam in the world. This study examines two Muslim American novels: Khaled Hosseini’s The Kite Runner (2003), and Mohja Kahf’s The Girl in the Tangerine Scarf (2006) to explore and explicate the processes underlying religious identity construction. The study also attempts to explain how these fictional texts can be read as countering the representations of Islam in the West and how they variously write back to dominant Western discourses about Islam and Muslim communities. Therefore, it is important to start this study with a brief historical overview on Muslim Americans immigration, an analysis of the socio-psychological theories of identity formation and identification, and the second generation’s religious commitment and religiosity. The second chapter deals with Khaled Hosseini’s debut novel The Kite Runner (2003) by presenting and introducing the Afghan culture and traditions, and showing how the identity of Amir the protagonist goes through identity forming moments. While the last chapter focuses on Mohja Kahf’s The Girl in the Tangerine Scarf (2006) whose main protagonist struggles to identify herself within her family and community and who at a certain moment starts to doubt her religious faith. The study comes out to the conclusion that post 9/11 Muslim American literature has engaged, deeply, in questions of making the cultural and religious identity. And that the process of identity formation is highly affected by religious traditions